The Readiness of Local Governments in Indonesia in Implementing Talent Management Policies - Fitriyani, Aliyyah Damar; Salomo, Roy Valiant (Journal of Public Representative and Society Provision, 2025)
This study analyzes the readiness of local governments in Indonesia to implement talent management policies as part of bureaucratic reform, using the Organizational Readiness for Implementing Change (ORIC) theory. Although regulated under Permen PANRB No. 3 of 2020, policy implementation still faces challenges, including lack of leadership commitment, limited infrastructure, and organizational culture resistance. The research employs a qualitative literature review, analyzing policy documents, government reports, and prior studies. Findings reveal varying levels of readiness among regions West Java and Pontianak City have adopted digital talent mapping systems, while others still rely on less effective traditional methods. Key success factors include leadership support, transparent meritocracy, and human resource and IT readiness. Strengthening regulatory harmonization and digitizing personnel systems are expected to optimize policy implementation, enhancing the professionalism of State Civil Apparatus (ASN) and the effectiveness of regional bureaucracy.